A Small Beautiful Example of Sustainability in the Heart of Zimbabwe - Venkatesh, G (Studia Ecologiae et Bioethicae, 2023)
Zimbabwe has diligently started pursuing the Sustainable Development Goals (SDGs) defined by the United Nations in 2015. While making progress and being aware of it, will be a shot in the arm, with success breeding more success, the journey may seem daunting at times. However, the journey – sustainable development towards the targets set - is what matters more than the final destination, as philosophers and savants often remind us. This article, while dwelling on sustainable development in this southern-African landlocked country in general, presents a beautiful example of a collaborative venture, undertaken by dedicated and determined international partners, and predicated on SDG#4 (Quality Education) and SDG#5 (Gender Equality), and harnessing the complementarities and synergies with the other SDGs, which set root during the COVID-pandemic, in Mwenezi in southern Zimbabwe. The pandemic while being a scourge, tended to have some silver linings to it, as it gave birth to many collaborations and made human beings realise that one’s own happiness is dependent to a very great extent on that of others. This venture emphasizes girls’ education and skills-development, which open the doors, synergistically, to sustained growth, development and progress. Education, indisputably, is a key component of the freedom necessary to live a life of value. To quote Nelson Mandela, ‘It is the most powerful weapon which you can use to change the world.”